Plan of the Kyuouot Indian Reserves, Rupert District ... - Surveyor General Of British Columbia (University of Victoria Libraries, 2023)
Surveyed and drawn by F.A. Devereux, 1892-1893. [Signed by P. O'Reilly, Indian Reserve Commissioner, no date.] [Approved by F.G. Vernon, Chief Commissioner of Lands and Works, 16 May 1894.] Map showing numerous Reserves in the areas around the Kyuquot Sound including Village Island No. 1; Mission Island No. 2; Ah-Mac-In-Nit Reserve No. 3; Granite Island Reserve No. 4; Ya-Kats Reserve No. 5; Houp-Si-Tas Reserve No. 6; Cha-Miss Reserve No. 7; Ka-Youk Reserve No. 8; Ka-Shittle Reserve No. 9; Ka-Oo-Winch Reserve No. 10; Tah-Sish Reserve No. 11; Art-Lish Reserve No. 12; Ka-Ouk Reserve No. 13; Mar-Kale Reserve No. 14; A-Mai Reserve No. 15; and Mach-Ta Reserve No. 16. A reference map is also included as an inset map showing the key plan location of all the reserves in this area. ...